Baker’s Yeast: Industrial Applications And Health Benefits (Applied Biological Research, 2019)
Baker’s yeast is used as a leavening agent in bread baking as it converts simple  fermentable sugars in dough to CO2 and ethanol. Fermentation by yeast leads  to the expansion of dough, its maturation and development of characteristic  flavours in cereal-based products. Different strains of yeasts like Saccharomyces cerevisiae, S. exiguous, S. boulardii, etc. are widely used in nourishment and  pharmaceutical industry. Yeast is a source of vitamin B, minerals, β-glucan  fiber and protein and is used as health supplement. As probiotic, it plays a vital role in folate biofortification, detoxification and bioavailability of nutrients. Anti-cholesterolemic, anti-mutagenic, anti-oxidative and anti-tumuor potential  of S. cerevisiae is currently under investigation. Yeast is exploited in several  industrial processes including bioethanol production and bioremediation and is  an excellent tool for biotechnological applications. This paper reviews the work  done on baker’s yeast and its industrial application and health benefits.
Keywords: Anticancer; bioremediation; health supplement; probiotic; yeast